Der Aktionär ist das grösste Säugetier - Staeck, Klaus
Wirtschaft;Unternehmen und Wettbewerb;Unternehmensorganisation;Unternehmensstruktur;Geschäftsteilhaber/in;Aktionär/in Wirtschaft;Wirtschafts- und Handelsverkehr;Handel;internationaler Handel;Nord-Süd-Handel Wirtschaft;Wirtschafts- und Handelsverkehr;Vermarktung (allgemein);Handelsgeschäft